Preliminary experience using MR-guided adaptive radiotherapy in head and neck cancer - Atienza, Caiden; Shepard, Andrew; Uzomah, Uwajachukwumma; Rajan, Shri Kiriti; Anderson, Carryn M.; Katzer, Joel; Rusu, Samuel; St-Aubin, Joel; Smith, Blake; Hyer, Daniel (Frontiers in Oncology, 2024)
This retrospective study evaluates the dosimetric benefits of adaptive radiotherapy for head and neck cancer patients. Five patients with node-positive oropharyngeal squamous cell carcinoma were treated with MR-guided radiotherapy using the Elekta Unity MR-Linac, undergoing 3-4 offline adaptive plan modifications during their treatment. This study compared the dose delivered to organs at risk (OARs) in a full offline adaptive approach versus an approach accounting only for daily setup. Results demonstrated a reduction in mean dose to critical structures in the offline adaptive arm. For example, the pharynx avoidance structure showed mean dose reductions ranging from 1.4 Gy to 3.6 Gy, and the left parotid gland exhibited reductions from 1.5 Gy to 1.9 Gy. Overall, offline adaptive radiotherapy reduced the mean cumulative dose to OARs in 19 of the 23 evaluated structures. Despite some instances of higher doses, the offline adaptive approach generally resulted in lower cumulative doses, emphasizing its potential to mitigate radiation-induced side effects. These findings suggest that offline adaptive radiotherapy has the potential to enhance treatment efficacy by better accommodating anatomical changes during therapy, thereby improving patient outcomes and reducing treatment-related morbidity.